Zeolite-supported transition metal catalysts to enhance the ozonation of aqueous phenol - Man Singh, Harjit Kaur (2005)
In this research, zeolite HZSM-5, H-ÃŸ, H-Mordenite and H-USY were used to evaluate the aqueous phenol and its corresponding chemical oxygen demand (COD) removals in a semi-continuous ozonation system. Screening for the best zeolite was held at different levels of phenol concentration (100 to 3340 ppm), temperature (30 to 70oC), ozonated air flow rate (0.5 to 1.5 L/min) and pH (5 to 9). The phenol adsorption tests were also performed. Results revealed that the presence of zeolites, except H-Mordenite, induced better results in terms of phenol and COD removals than ozonation alone. HZSM-5 (80) and H-USY were the most promising zeolites to treat phenol less and above 750 ppm of phenol, respectively. HZSM-5 (80) and HUSY were also found to be the best phenol adsorbents at 100 and 3340 ppm phenol, respectively. Effect of variables showed that the removal of phenol is almost independent of temperature at 100 ppm phenol, but very much affected by the ozonated air flow rate and pH at both the concentration levels. The study on HZSM-5 (80) was sustained by impregnating transition metals (Ti, Mn, Fe and Cu) onto it to improve its activity in ozonation of phenol. Based on the results obtained, a 2 wt.% Mn/HZSM-5 is the most promising catalyst with phenol and COD removals of 95.78% and 70.17%, respectively in two hours. In addition, ozonation tests were also carried out using GAC and alumina in order to compare the effectiveness of phenol treatment with different groups of catalysts. The tests with alumina indicated that although it inherits a poor adsorption capacity, its activity was tremendously enhanced in the presence of ozone. Whereas, for GAC, its combination with ozone for phenol treatment produced a more significant improvement with total phenol elimination and a more complete COD removal in two hours of treatment compared to alumina, HZSM-5 (80) and Mn/HZSM-5. In all the ozonation systems tested, adsorption of phenol by the zeolites and GAC was observed to play a vital role in determining their activity in phenol and COD removals.